(untitled) (Academicia Globe: Inderscience Research, 2021)
At the end of the last century, two important events took place in the life of the Uzbek people. One gained language independence on October 21, 1989, and the other gained state independence on September 1, 1991. The independence of language has given a new impetus to the consciousness of our people. We are beginning to understand ourselves. It has been proved that textbooks and manuals can be written in Uzbek in all areas. The emergence of visual aids is one of the pragmatic features of language. The study of the linguistic means of a work of art is closely connected with the study of the richness of language, including the style of the writer.